Infrared Surface Brightness Fluctuation Distances for MASSIVE and Type Ia Supernova Host Galaxies* - Jensen, Joseph B.; Blakeslee, John P.; Ma, Chung-Pei; Milne, Peter A.; Brown, Peter J.; Cantiello, Michele; Garnavich, Peter M.; Greene, Jenny E.; Lucey, John R.; Phan, Anh; Tully, R. Brent; Wood, Charlotte M. (The Astrophysical Journal Supplement Series, 2021)
We measured high-quality surface brightness fluctuation (SBF) distances for a sample of 63 massive early-type galaxies using the WFC3/IR camera on the Hubble Space Telescope. The median uncertainty on the SBF distance measurements is 0.085 mag, or 3.9% in distance. Achieving this precision at distances of 50–100 Mpc required significant improvements to the SBF calibration and data analysis procedures for WFC3/IR data. Forty-two of the galaxies are from the MASSIVE Galaxy Survey, a complete sample of massive galaxies within ∼100 Mpc; the SBF distances for these will be used to improve the estimates of the stellar and central supermassive black hole masses in these galaxies. Twenty-four of the galaxies are Type Ia supernova hosts, useful for calibrating SN Ia distances for early-type galaxies and exploring possible systematic trends in the peak luminosities. Our results demonstrate that the SBF method is a powerful and versatile technique for measuring distances to galaxies with evolved stellar populations out to 100 Mpc and constraining the local value of the Hubble constant.
EPrint Processing Status: Full text deposited in DRO